Matrine attenuates high‐fat diet‐induced in vivo and ox‐LDL‐induced in vitro vascular injury by regulating the PKCα/eNOS and PI3K/Akt/eNOS pathways. Issue 4 (15th February 2019) - Zhang, Song; Guo, Shun; Gao, Xiao‐bo; Liu, An; Jiang, Wei; Chen, Xi; Yang, Peng; Liu, Lin‐na; Shi, Lei; Zhang, Yan
Abstract: Lipid metabolism disorders lead to vascular endothelial injury. Matrine is an alkaloid that has been used to improve obesity and diabetes and for the treatment of hepatitis B. However, its effect on lipid metabolism disorders and vascular injury is unclear. Here, we investigated the effect of matrine on high‐fat diet fed mice and oxidized low‐density lipoprotein (ox‐LDL)‐induced human umbilical vein endothelial cells (HUVECs). Computational virtual docking analyses, phosphoinositide 3‐kinase (PI3K) and protein kinase C‐α (PKCα) inhibitors were used to localize matrine in vascular injuries. The results showed that matrine‐treated mice were more resistant to abnormal lipid metabolism and inflammation than vehicle‐treated mice and exhibited significantly alleviated ox‐LDL‐stimulated dysfunction of HUVECs, restored diminished nitric oxide release, decreased reactive oxygen species generation and increased expression phosphorylation of AKT‐Ser473 and endothelial nitric oxide synthase (eNOS)‐Ser1177. Matrine not only up‐regulates eNOS‐Ser1177 but also down‐regulates eNOS‐Thr495, a PKCα‐controlled negative regulator of eNOS. Using computational virtual docking analyses and biochemical assays, matrine was also shown to influence eNOS/NO via PKCα inhibition. Moreover, the protective effects of matrine were significantly abolished by the simultaneous application of PKCα and the PI3K inhibitor. Matrine may thus be potentially employed as a novel therapeutic strategy against high‐fat diet‐induced vascular injury.